Repeated subcutaneous administrations of krokodil causes skin necrosis and internal organs toxicity in Wistar rats: putative human implications - Alves, Emanuele Amorim; Brandão, Pedro; Neves, João Filipe; Cravo, Sara Manuela; Soares, José Xavier; Grund, Jean-Paul C; Duarte, José Alberto; Afonso, Carlos M M; Pereira Netto, Annibal Duarte; Carvalho, Félix; Dinis-Oliveira, Ricardo Jorge (Human psychopharmacology, 2017)
OBJECTIVE: "Krokodil" is the street name for an impure homemade drug mixture used as a cheap substitute for heroin, containing desomorphine as the main opioid. Abscesses, gangrene, thrombophlebitis, limb ulceration and amputations, jaw osteonecrosis, skin discoloration, ulcers, skin infections, and bleeding are some of the typical reported signs in humans. This study aimed to understand the toxicity of krokodil using Wistar male rats as experimental model. METHODS: Animals were divided into seven groups and exposed subcutaneously to NaCl 0.9% (control), krokodil mixture free of psychotropic substances (blank krokodil), pharmaceutical grade desomorphine 1 mg/kg, and four different concentrations of krokodil (containing 0.125, 0.25, 0.5, and 1 mg/kg of desomorphine) synthesized accordingly to a "domestic" protocol followed by people who inject krokodil (PWIK). Daily injections for five consecutive days were performed, and animals were sacrificed 24 hr after the last administration. Biochemical and histological analysis were carried out. RESULTS: It was shown that the continuous use of krokodil may cause injury at the injection area, with formation of necrotic zones. The biochemical results evidenced alterations on cardiac and renal biomarkers of toxicity, namely, creatine kinase, creatine kinase-MB, and uric acid. Significant alteration in levels of reduced and oxidized glutathione on kidney and heart suggested that oxidative stress may be involved in krokodil-mediated toxicity. Cardiac congestion was the most relevant finding of continuous krokodil administration. CONCLUSIONS: These findings contribute notably to comprehension of the local and systemic toxicological impact of this complex drug mixture on major organs and will hopefully be useful for the development of appropriate treatment strategies towards the human toxicological effects of krokodil.
Keywords: Liver; Tissue Distribution; Rats; játra; phosphorous; kodein; mužské pohlaví; Rats, Wistar; zakázané drogy; Analgesics, Opioid; Necrosis; Oxidative Stress; opioidní analgetika; toxicity; Skin Diseases; Injections, Subcutaneous; krysa rodu Rattus; Organ Size; velikost orgánu; zvířata; plíce; tkáňová distribuce; Humans; kožní nemoci; Illicit Drugs; ledviny; krokodil; Heart; nekróza; Codeine; potkani Wistar; Kidney; oxidační stres; in vivo; injekce subkutánní; desomorphine; Lung; srdce; lidé; Male; Animals